International Dimensions of Humanitarian Law (Human Rights and Humanitarian Law - Book Archive pre-2000., 1988)
Commissioned by UNESCO from the Henry Dunant Institute, this volume of essays lays the foundation for an international programme for the teaching of international humanitarian law within the framework of UNESCO's plan for the development of the teaching of human rights. Parts I and II deal with the development of humanitarian ideas and law within different schools of thought and cultural traditions; Part III with the law of armed conflict and Part IV with the application of international humanitarian law. It is hoped that the publication of this volume, which, in its original French edition, coincided with the 40th Anniversary of UNESCO and the International Year of Peace proclaimed in 1986 by the UN General Assembly, will reinforce the determination of the international community to achieve the aim of the founders of UNESCO, namely to construct the defences of peace in the minds of men.